Thermal study of the modular high-temperature gas-cooled reactor - Antonella Lombardi Costa; Mario Cerrogrande Ramos; Vitor Vasconcelos Araújo Silva; Claubia Pereira; Maria Auxiliadora Fortini Veloso (Brazilian Journal of Radiation Sciences)
The Modular High-Temperature Gas-Cooled Reactor (MHTGR) is an advanced power plant being a coupling between a modular helium cooled reactor and a gas turbine. The gas-cooled reactor types are of great interest due to their potential to provide high-temperature process heat in addition to their high thermal-to-electric power conversion efficiency and inherent safety features. The MHTGR is helium-cooled, graphite-moderated and uses Triso-coated fuel particles immersed in a cylindrical-shaped graphite matrix. The annular core and fuel blocks are based on the FSV (Fort Saint Vrain) reactor design.  In this work, a MHTGR model developed in the RELAP5-3D code is presented, as well as its verification for steady state calculations. The core simulations have been performed to three power values: 350, 450 and 600 MWth. The heat transfer along the blocks was investigated taking into account the diversion flow. The radial power distribution within the compact fuel was assumed to be uniform for the analysis. Radial and axial normalized power factors were specified for each axial segment in the heat structures that are coupled to the thermal hydraulic channels that shape the reactor core.  In the analyses, coolant and fuel temperatures, pressure drop and mass flow rate were verified at steady state conditions. The results were very close to the reference ones demonstrating that the developed model is capable to reproduce the MHTGR core in steady state operation.